Rethinking Nasserism : revolution and historical memory in modern Egypt - Podeh, Elie; Winckler, Onn (University Press of Florida, 2004)
''An enormous amount of academic literature has been published on Nasserism since the 1950s and, to my mind, Rethinking Nasserism is without a doubt the last word on the subject. ... An outstanding reappraisal of Nasserism as a major force in the 20th-century Middle East.